2022
DOI: 10.1530/rep-21-0428
|View full text |Cite
|
Sign up to set email alerts
|

The role of angiotensin II and relaxin in vascular adaptation to pregnancy

Abstract: During pregnancy, systemic and uteroplacental blood flow increase to ensure an adequate blood supply that carries oxygen and nutrients from the mother to the fetus. This results in changes to the function of the maternal cardiovascular system. There is also a pregnancy-induced vasodilation of blood vessels, which is known to have a protective effect on cardiovascular health/function. Additionally, there is evidence that the effects of maternal vascular vasodilation are maintained post-partum, which may reduce … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 114 publications
0
6
0
Order By: Relevance
“…7,15 Many cardiovascular adaptations of pregnancy are mediated by vascular signalling changes. 16,17 People with SCD have well described vascular damage and aberrant vascular responsiveness 18,19 which may limit their physiological adaptations to pregnancy. Previous studies have demonstrated abnormally low prostaglandin to thromboxane ratios during pregnancy in people with HbSS compared to unaffected pregnancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,15 Many cardiovascular adaptations of pregnancy are mediated by vascular signalling changes. 16,17 People with SCD have well described vascular damage and aberrant vascular responsiveness 18,19 which may limit their physiological adaptations to pregnancy. Previous studies have demonstrated abnormally low prostaglandin to thromboxane ratios during pregnancy in people with HbSS compared to unaffected pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…People with SCD, especially those with HbSS/HbSβ 0 , have high cardiac output and low systemic vascular resistance at baseline, which may limit capacity to adapt further in pregnancy 7,15 . Many cardiovascular adaptations of pregnancy are mediated by vascular signalling changes 16,17 . People with SCD have well described vascular damage and aberrant vascular responsiveness 18,19 which may limit their physiological adaptations to pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These alterations in the wound healing process result in a disturbed mechanical status of the skin, stimulating the development of keloids with unusual characteristics and in uncommon body sites. 19,20 Pregnancy is believed to worsen pre-existing keloids or hypertrophic scars and may even trigger a previous scar to evolve into a keloid scar. 21 (Figure 3).…”
Section: Pregnancy and Hormonal Effectsmentioning
confidence: 99%
“…Skin changes involve modifications in the dermis and its vascular network, leading to an increase in the total volume of circulating blood and promoting skin inflammation. These alterations in the wound healing process result in a disturbed mechanical status of the skin, stimulating the development of keloids with unusual characteristics and in uncommon body sites 19,20 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation